2004
DOI: 10.1002/ajh.20127
|View full text |Cite
|
Sign up to set email alerts
|

Cardiobacterium hominis endocarditis associated with very severe thrombocytopenia and platelet autoantibodies

Abstract: Severe thrombocytopenia is a life-threatening condition. It is often associated with immune-mediated platelet destruction or myeloablative chemotherapy. Infective endocarditis has been associated with thrombocytopenia, which, as in sepsis, tends to be mild and is often the result of several pathological mechanisms. We report a case of Cardiobacterium hominis endocarditis associated with very severe thrombocytopenia and bleeding in a patient who refused platelet transfusion. Platelet autoantibodies directed aga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 33 publications
0
15
0
Order By: Relevance
“…In a study 29 in humans, an immunocompromised state was associated with a 2.9-times greater risk of adverse outcome in intensive care unit patients with IE, and in another study, 25 concurrent diabetes mellitus was an independent predictor of death. 39 In the present study, only 1 dog had a normal CBC; that dog had a diagnosis of possible IE, no microbial growth on culture of blood, and underlying congenital cardiac disease. 10 Leukocytosis and hypoalbuminemia were more common laboratory abnormalities in dogs with IE than in humans with IE 1 and were findings observed in nearly all dogs.…”
Section: Discussionmentioning
confidence: 51%
“…In a study 29 in humans, an immunocompromised state was associated with a 2.9-times greater risk of adverse outcome in intensive care unit patients with IE, and in another study, 25 concurrent diabetes mellitus was an independent predictor of death. 39 In the present study, only 1 dog had a normal CBC; that dog had a diagnosis of possible IE, no microbial growth on culture of blood, and underlying congenital cardiac disease. 10 Leukocytosis and hypoalbuminemia were more common laboratory abnormalities in dogs with IE than in humans with IE 1 and were findings observed in nearly all dogs.…”
Section: Discussionmentioning
confidence: 51%
“…In a recent review, the mean duration of symptoms before diagnosis was found to be 145 days (range 1 week to 11 months) 7. Laboratory findings do not differ from endocarditis caused by other organisms 7 9 18. The most common physical findings are a cardiac murmur (94%), peripheral embolic lesions (51%) and splenomegaly (40%) 9.…”
Section: Discussionmentioning
confidence: 88%
“…Surgical treatment, mostly valve replacement, was needed in 45% of published cases 7. The main complications of C hominis endocarditis include congestive heart failure, peripheral embolic events, arrhythmia, mycotic aneurysm, glomerulonephritis, vertebral osteomyelitis and severe thrombocytopoenia 9 18. The clinical outcome of C hominis endocarditis is favourable, in almost 95% of reported cases the patients were cured 6–7 9.…”
Section: Introductionmentioning
confidence: 99%
“…Since infective endocarditis is known to be associated with continuous, low grade bacteremia, one would have expected to diagnose endocarditis due to most agents known to cause subacute bacterial endocarditis (e.g., Streptococci or Enterococcus spp.). The HACEK group of organisms were previously difficult to isolate by routine blood culture methods, but with modern culture techniques these organisms are usually isolated within three to five days [20, 21]. …”
Section: Discussionmentioning
confidence: 99%